1998
DOI: 10.1002/(sici)1097-0177(199806)212:2<181::aid-aja4>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale screening for developmental genes in embryonic stem cells and embryoid bodies using retroviral entrapment vectors

Abstract: Mammalian development is orchestrated by a variety of cellular proteins with expression that is regulated precisely. Although some of the genes encoding these factors have been identified, largely by homology to those of simpler organisms, the majority of them presumably remain unknown. We report here on the results of a large‐scale genetic screen that can potentially lead to the identification of many of these unidentified genes in mice. The method we developed takes advantage of the fact that many of the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…13,15 Its restricted expression during embryogenesis in the vascular endothelium and its precursors in the yolk sac blood islands suggested that Egfl7 plays a role during endothelial lineage determination, and possibly during embryonic vasculogenesis and angiogenesis. Egfl7-specific transcripts were found in most adult organs tested, and in primary and transformed endothelial cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,15 Its restricted expression during embryogenesis in the vascular endothelium and its precursors in the yolk sac blood islands suggested that Egfl7 plays a role during endothelial lineage determination, and possibly during embryonic vasculogenesis and angiogenesis. Egfl7-specific transcripts were found in most adult organs tested, and in primary and transformed endothelial cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In a genetic screen for early circulatory system genes 13,14 we have identified a novel murine gene, epidermal growth factor (EGF)-like domain 7 (Egfl7). 15 Egfl7 encodes a secreted protein with an apparent molecular weight of ϳ41 kd that contains an aminoterminal signal peptide and two centrally located EGF domains.…”
mentioning
confidence: 99%
“…3,36 Briefly, ES cells were dissociated into single cells with 0.25% Trypsin/EDTA (Gibco/BRL). After MEF feeder cells were depleted by incubating cell suspensions for 10 minutes at 37°C, ES cells were suspended and counted by Trypan Blue staining (Bioss, Beijing, China).…”
Section: Es Cell Culture and Differentiationmentioning
confidence: 99%
“…36 Transfected ES cells were placed on neomycin-resistant SNL (STO [mouse embryonic fibroblast cell line] that produces LIF) feeder cells (a gift from Dr K. Choi) in the ES cell medium. After 24 hours, ES cells were selected in the ES medium supplemented with 0.25 mg/mL G418 (Geneticin Selective Antibiotic; Invitrogen, Carlsbad, CA) for 10 days.…”
Section: Generation Of Stable Lycat Transgenic Es Cell Linesmentioning
confidence: 99%
“…The ability to differentiate ES cells in vitro allows for their use as model systems for the study of developmental potential and also as valuable reagents for stem cell therapeutic approaches [22][23][24]. The method proposed here is an efficient in vitro system to screen and study effects of small molecules and bioagents.…”
Section: Discussionmentioning
confidence: 99%